PENGARUH HUTANG JANGKA PENDEK DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PADA PT WIDJAYA DJAYA INDAH DI KOTA BATAM: Current Ratio; Company Size; Return On Assets. - Dian Efriyenty (JURNAL AKUNTANSI BARELANG, 2020)
This study aims to examine the effect of short-term debt and firm size on profitability at PT Widjaya Djaya Indah, located in Batam City. This research uses quantitative methods. The data collection technique in this study used a saturated sample technique, namely using the entire data obtained. The data analysis method used is descriptive analysis, classic assumption test which includes normality test, multicolonierity test, heterocedastity test and autocorrelation test, hypothesis test which includes t test, f test, determination coefficient test and multiple linear regression. The sample used is 60 financial statement data from PT Widjaya Djaya Indah and the research objects used are the current ratio (X1), company size (X2), and return on assets (Y). The data in this study were processed using SPSS version 21. The results of the F test processing in this study indicate that simultaneously there is a positive and significant effect between the current ratio and company size on return on assets at PT Widjaya Djaya Indah. And the t test results show that the current ratio has a positive and significant effect on return on assets while company size has a negative and significant effect on return on assets.